Conceptual Shifts in the Post-Non-Classical Philosophical Understanding of Dialogue: Developing Cultural-Educational Space - Troitska, Olena; Sinelnikova, Valentina; Matsko, Vitalii; Vorotniak, Liudmyla; Fedorova, Olesia; Radzyniak, Tetiana (My University, 2022)
In the scientific literature, there are accents that emphasize certain changes in the functioning of philosophy, which took place in connection with the establishment of the postulates of postmodernism as a new period in the development of culture, as a style of post nonclassical scientific thinking, in fact, the content and hierarchy of values positions itself with a sophisticated departure from the classical and non-classical philosophical reflection. Philosophical and educational understanding of the methodology of research of dialogue and tolerance testified to the relevance of their research in the development of the potential of today’s multicultural education and its growth in the cultural and educational space. Dialogue, dialogics and tolerance are represented by the mechanisms of meaning-making, axiology and praxeology: dialogical cognition of the interpersonal, social-group, societal, planetary world provides a certain "breakthrough" in the worldview-value coordinate system, in externalinternal control of growth efficiency and its spiritual dimension. The axiological, ontological, educational-epistemological aspects of “fitting” a person into a new world context are precisely in the plane of philosophy, enriching the cultural fields of today’s education through integration in goal-setting, content, organizational and managerial conditions for teaching and upbringing value ideals, principles, methods of holistic study of a person and those that are relevant today and provide Homo educandus with a meaning-making knowledge.
Keywords: post-nonclassical science; post-nonclassical methodology; postmodernist "departure"; educational discourse; cultural and educational space; philosophical methodology; philosophical methodology